Curved shape memory alloy-based soft actuators and application to soft gripper. (15th September 2017) - Rodrigue, Hugo; Wang, Wei; Kim, Dong-Ryul; Ahn, Sung-Hoon
Abstract: The performance of shape-memory alloy (SMA)-based soft actuators depends largely on the configuration of the cross-section of the actuator. A shape memory alloy-based curved bending actuator manufactured by double casting is introduced in this work. Curved actuators are capable of larger maximum bending angles with the same cross-section configuration as a straight actuator, and both the design method and the casting method proposed in this work are novel for this type of actuator. The effect of the initial bending angle due to the curvature of the actuator and of non-uniform initial curvatures on the maximum bending angle was tested. A model based on the thermoconstitutive model of SMA with a geometrical analysis of the deformation of the actuator was used to estimate the effect of the initial curvature on the maximum bending angle of the actuator. Finally, multiple curved actuators were implemented as a simple gripper and the lifting force of straight and curved actuators were compared, and the curved gripper has a lifting force nearly three times larger than the straight gripper. This type of concept can be used to tailor the force, deformed shape and maximum deformation of SMA actuators.